Write an expression to describe the sequence -3, -6, -9, -12,... Use n to represent the position of a term in the sequence, where n=1 for the first term.

*The sequence -3, -6, -9, -12,... looks like 1, 2, 3, 4,... except each term is multiplied by -3. So, the formula is -3n, where n represents the position of a term in the sequence.*

*Check the first four terms:*

*To find the 1*^{st} term, plug in n=1.

*-3n=-3(1)*=-3

*To find the 2*^{nd} term, plug in n=2.

*-3n=-3(2)*=-6

*To find the 3*^{rd} term, plug in n=3.

*-3n=-3(3)*=-9

*To find the 4*^{th} term, plug in n=4.

*-3n=-3(4)*=-12

*The sequence -3, -6, -9, -12,... is described by the expression -3n*

Write an expression to describe the sequence -7, -6, -5, -4,... Use n to represent the position of a term in the sequence, where n=1 for the first term.

*The sequence -7, -6, -5, -4,... looks like 1, 2, 3, 4,... except each term is 8 smaller. So, the formula is n-8, where n represents the position of a term in the sequence.*

*Check the first four terms:*

*To find the 1*^{st} term, plug in n=1.

*n-8=1-8*=-7

*To find the 2*^{nd} term, plug in n=2.

*n-8=2-8*=-6

*To find the 3*^{rd} term, plug in n=3.

*n-8=3-8*=-5

*To find the 4*^{th} term, plug in n=4.

*n-8=4-8*=-4

*The sequence -7, -6, -5, -4,... is described by the expression n-8.*